Divergence in the shell morphology of the land snail genus Aegista (Pulmonata: Bradybaenidae) under phylogenetic constraints. (26th November 2014) - Hirano, Takahiro; Kameda, Yuichi; Kimura, Kazuki; Chiba, Satoshi
<x xml:space="preserve">Abstract</x> The role of natural selection in phenotypic evolution is central to evolutionary biology. Phenotypic evolution is affected by various factors other than adaptation, and recent focus has been placed on the effects of phylogenetic constraints and niche conservatism on phenotypic evolution. Here, we investigate the relationship between the shell morphology and habitat use of bradybaenid land snails of the genus Aegista and clarify the causes of the divergence in shell morphology among phylogenetically related species. The results of ancestral state reconstruction showed that arboreal species have evolved independently from ground‐dwelling species at least four times. A significant association was found between shell shape and habitat use, despite the existence of a certain degree of phylogenetic constraint between these traits. A principal component analysis showed that arboreal species tend to have a relatively high‐spired shell with a narrow umbilicus. By contrast, ground‐dwelling species have a low‐spired shell with a wide umbilicus. Although the latitude and elevation of the sampling locations showed no relationship with shell morphology, the geology of the sampling locations affected the shell size of arboreal species. The development of a well‐balanced shell shape is one effective method for reducing the cost of locomotion under the force of gravity in each life habitat, resulting in the divergence in shell morphology and the independent evolution of morphologically similar species among different lineages. The present study suggests that ecological divergence is probably the cause of shell morphology divergence in land snails. © 2014 The Linnean Society of London, Biological Journal of the Linnean Society, 2014, 114, 229–241.